Learning With A Saintific Approach On Students' Interests And Learning Outcomes In The Quadragous Function Material In Class X - Rumapea, Lenni Santana; Tambunan, Hardi; Sinaga, Samuel Juliardi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine the learning with a scientific approach to students' interests and learning outcomes in the quadratic function material at SMK Negeri 5 Medan 2024/2025. The type of research used is quantitative descriptive. The research population was all class X, and the research sample consisted of 64 class The sampling technique was carried out using the purposive sampling technique. The instruments used were tests, questionnaires and observation sheets. Hypothesis testing in this study used the t-test and descriptive test. The results of the study showed that: (1) learning with a scientific approach has an effect on students' learning interests, (2) the magnitude of the influence of learning with a scientific approach on students' learning interests is 73.7%, (3) learning with a scientific approach has an effect on students' learning outcomes, (4) the magnitude of the influence of learning with a scientific approach on students' learning outcomes is 89.9%, (5) learning with a scientific approach to students' learning interests is effective, (6) learning with a scientific approach to students' learning outcomes is effective.